2017
DOI: 10.18203/issn.2454-5929.ijohns20173033
|View full text |Cite
|
Sign up to set email alerts
|

Solitary nodule thyroid: diagnosis and management

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Solitary nodule can be a true solitary nodule or a dominant nodule of multinodular goitre or ectopic thyroid or unilateral agenesis. Solitary nodule can be benign or malignant. Purpose of evaluation is to differentiate between the two. </span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">A prospective study of solitary nodule thyroid (STN) patients presenting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…In our study, on clinical examination and correlating it with ultrasonographic findings, it was found that majority of the patients presented with bilateral swelling (54%), followed by unilateral swelling (34%) and few (12%) had swelling in the midline, which differed from other studies with swelling frequent unilaterally. In our study in unilateral swellings, the swelling was frequently found in right lobe of thyroid (22%) and only 12% swelling were present in left thyroid lobe, which was similar to the findings of Vyas et al and Deepthi et al 7,8 On USG, in our study, colloid nodule was the commonest thyroid swelling followed by MNG, which differed from that found by Santosh et al…”
Section: Discussionsupporting
confidence: 90%
“…In our study, on clinical examination and correlating it with ultrasonographic findings, it was found that majority of the patients presented with bilateral swelling (54%), followed by unilateral swelling (34%) and few (12%) had swelling in the midline, which differed from other studies with swelling frequent unilaterally. In our study in unilateral swellings, the swelling was frequently found in right lobe of thyroid (22%) and only 12% swelling were present in left thyroid lobe, which was similar to the findings of Vyas et al and Deepthi et al 7,8 On USG, in our study, colloid nodule was the commonest thyroid swelling followed by MNG, which differed from that found by Santosh et al…”
Section: Discussionsupporting
confidence: 90%
“…Also, 7.5% had total thyroidectomy with nodal dissection. Deepthi Met al [7] in their study similar to our study observed that hemithyroidectomy was done in 74% of benign STN 65patients and a total thyroidectomy was done in malignant nodule and MNG patients and followed-up by lifelong L-T4 therapy. They concluded that "Small benign solitary nodules regress with medical therapy alone.…”
Section: Type Of Surgerysupporting
confidence: 81%
“…In our study only 13.8% of the nodules were malignant. The incidence of malignancy was only 7.46% in the study by Deepthi Met al [7]. In the study by FNAC showed that 14% of the nodules were malignant.…”
Section: Fnacmentioning
confidence: 85%